Niches of dominant fish in the waters surrounding the Taishan Islands, China - 杨璐 陈杰 杨圣云 钟慧琪 鞠培龙 杨顺良 孙芹芹 陈明茹 (Chinese journal of oceanology and limnology, 2016)
An index of relative importance（IRI） was employed to screen for dominant fish in the waters surrounding the Taishan Islands, China, using data from four seasonal trawl surveys undertaken between 2012 and 2013. Niche breadth and niche overlap were measured using the Feinsinger and Morisita-Horn indices, respectively, and the characteristics and seasonal variations in the niches of dominant fish were assessed via non-metric multidimensional scaling（NMDS） and cluster analysis. A total of 80 fish species, including 16 dominant species, were recorded. Only A mblychaeturichthys hexanema was dominant in all seasons. According to niche breadth values and NMDS, the 16 dominant species were grouped into the following three types：（1） wide niche breadth species, including Cynoglossus macrolepidotus, A. hexanema, and Trypauchen vagina, among others;（2） medium niche breadth species, including Setipinna taty and Johnius belangerii; and（3） narrow niche breadth species, including A trobucca nibe and Coilia mystus. Most species with a wider niche breadth were demersal fish with a lower swimming capability and even distribution. The niche breadth of migrating fish was narrower than that of settled fish. At a given spatial scale, fish with stronger swimming capabilities had a narrower niche breadth. Niche overlap, which is associated with niche specialization, ranged from 0.000 to 0.886 and had an annual mean value of 0.314. In summer and autumn, niche overlap was relatively high within species of the Sciaenidae family and within species of the Gobiidae in autumn. Dif ferences in thermophily, feeding habits, food organism abundance/distribution and predator-prey relationships af fected the niche overlap of fish in this area. Cluster analysis revealed that species with the narrowest niche breadth and lowest niche overlap values usually displayed lower aggregation and greater distribution dif ferences compared with other species.